Transformasi Budaya Akademik Mahasiswa Pendidikan Agama Islam pada Era Digital: Studi Penggunaan SIAAP di Pascasarjana UIN Prof. K.H Saifuddin Zuhri Purwokerto - Ana Aulia Hanifah (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the transformation of the academic culture of students of the Islamic Religious Education (PAI) Postgraduate Study Program at UIN Prof. K.H. Saifuddin Zuhri Purwokerto in the digital era through the use of the Postgraduate Academic Administration Information System (SIAAP). The study uses a descriptive qualitative method with data collection through interviews and documentation. Data were analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the use of SIAAP has encouraged four forms of academic culture transformation, namely: (1) changes in academic administration from a manual system to an integrated digital service; (2) the growth of a culture of verification and transparency of academic information; (3) a shift in academic interaction patterns from direct communication to a blended pattern; and (4) the development of a digital ta'awun culture among students. This transformation is supported by automatic integration with Saizu Link and a simple interface design, while the main obstacle found is the technical instability of the system in the form of errors. From the perspective of Islamic values, SIAAP strengthens the values ​​of amanah, shidq, nizam, and itqan through transparency and regularity of academic services, while also fostering the value of shabr when students face technical obstacles. However, the digitalization of academic services also has the potential to reduce the intensity of face-to-face interactions in the Islamic scientific tradition and encourage instant expectations that are not in line with the values ​​of the modern era.